(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article aims to reflect about the importance of the Italian sign language (LIS) recognition as a minority language. Trying to consider the issues of pluralism, social cohesion, principles of solidarity and equality, the Author proposes a reconstruction of the Italian, European and international legal frameworks relating to the LIS. This situation shows how the articulation of the State form is still able to demonstrate the principle of equality (of the language) effectiveness. Finally, the Author reflects on the constitutional importance of the LIS recognition, also for the Republic cultural growth.